The Important Role of Work Motivation as Mediation and Work Discipline in Improving the Performance of Gresik Cooperative Employees - Prihastuti, Riza Ratna; Soelistya, Djoko; Wijayanti, Tri Cicik (Budapest International Research and Critics University, 2022)
Cooperatives are expected to be one of several economic actors and act as the main support for the national economy in order to provide the welfare of members and the community. In the last ten years, the Indonesian government has had a â€œtotal cooperative reformâ€ program which was translated through the stages of reorientation, rehabilitation and development,